Side Effects of Brand Ambassadors on Brands “s” - Kuswandi, Ignatius Richard; Kurniadi, Benedicta Alvina; Hundura, Rindina (Yayasan Ilomata, 2024)
BTS is a Korean boy band that is internationally renowned, with numerous fans across various countries, especially in Indonesia. BTS collaborates with various brands as brand ambassadors, one of them being Brand